An effective deep learning model for grading abnormalities in retinal fundus images using variational auto‐encoders. Issue 1 (2nd July 2022) - Sundar, Sumod; Sumathy, Subramanian
Abstract: Diabetic retinopathy (DR) and Diabetic Macular Edema (DME) are severe diseases that affect the eyes due to damage in blood vessels. Computer‐aided automated grading will help clinicians conduct disease diagnoses at ease. Experiments of automated image processing with deep learning techniques using CNN produce promising results, especially in the medical imaging domain. However, the disease grading tasks in retinal images using CNN struggle to retain high‐quality information at the output. A novel deep learning model based on variational auto‐encoder to grade DR and DME abnormalities in retinal images is proposed. The objective of the proposed model is to extract the most relevant retinal image features efficiently. It focuses on addressing less relevant candidate region generation and translational invariance present in images. The experiments are conducted in IDRID dataset and evaluated using accuracy, U‐kappa, sensitivity, specificity and precision metrics. The results outperform compared with other state‐of‐art techniques.